Forceps Biopsies Are Not Reliable in the Workup of Large Colorectal Lesions Referred for Endoscopic Resection: Should They Be Abandoned?. Issue 9 (September 2019) - Rönnow, Carl-Fredrik; Uedo, Noriya; Stenfors, Iréne; Toth, Ervin; Thorlacius, Henrik
Abstract : BACKGROUND: Biopsies are routinely obtained in the workup of large colorectal polyps before endoscopic resection. OBJECTIVE: This study aimed to examine how reliable biopsies are in terms of reflecting the true histopathology of large colorectal polyps, in the clinical routine. DESIGN: This is a retrospective study. SETTINGS: Data from patients undergoing polypectomy of large colorectal polyps at the endoscopy unit, Skåne University Hospital Malmö, between January 2014 and December 2016 were scrutinized. PATIENTS: A total of 485 colorectal lesions were biopsied within 1 year before complete endoscopic removal. Biopsy-obtained specimens were compared with completely resected specimens in terms of concordance and discordance and if the final result was upgraded or downgraded. MAIN OUTCOME MEASURES: The primary outcome measured was the concordance between biopsy-obtained specimens and completely resected specimens. RESULTS: Median lesion size was 3 cm (range 1–11). In 189 cases (39%), biopsies did not provide a correct dysplastic grade compared with final pathology after complete resection. One hundred forty-three cases (29%) and 46 cases (9%) were upgraded and downgraded. The percentage of cases with discordant biopsy results was 40% in cases with 1 biopsy taken and 38% in cases where multiple biopsies had been sampled. Time from biopsy to complete resection did not influence the erroneous outcome of biopsies. Notably, the percentage of discordant biopsy results was 37% and 35% in lesions measuring 1 to 2 cm and 2 to 4 cm. However, this percentage increased to 48% in colorectal lesions larger than 4 cm. LIMITATIONS: This study was designed to reflect the clinical routine, the number of biopsies obtained and forceps technique were hence not standardized, which constitutes a limitation. CONCLUSIONS: This study demonstrates that cancer-negative forceps biopsies of large colorectal polyps, referred for endoscopic resection, are not reliable. Considering that endoscopic resection of lesions containing superficial cancer is plausible, the clinical value of forceps biopsies in lesions suitable for endoscopic resection is questionable. See Video Abstract at http://links.lww.com/DCR/A984 . LAS BIOPSIAS CON FÓRCEPS NO SON CONFIABLES EN EL ESTUDIO DE LAS LESIONES COLORRECTALES GRANDES REFERIDAS PARA RESECCIÓN ENDOSCÓPICA: ¿DEBERÍAN ABANDONARSE?: ANTECEDENTES: Las biopsias se obtienen de forma rutinaria en el estudio de pólipos colorrectales grandes previo a resección endoscópica. OBJETIVO: Analizar que tan confiables son las biopsias en cuanto a reflejar la verdadera histopatología de los pólipos colorrectales grandes, en la rutina clínica. DISEÑO: Este es un estudio retrospectivo. AJUSTES: Los datos de pacientes sometidos a polipectomía de pólipos colorrectales grandes en la unidad de endoscopia, en Skåne University Hospital Malmö, entre enero de 2014 y diciembre de 2016 fueron examinados. PACIENTES: Un total de 485 lesiones colorrectales se biopsiaron dentro de un año antes de la resección endoscópica completa. Las muestras obtenidas mediante biopsia se compararon con las muestras completas resecadas en términos de concordancia y discordancia, y si el resultado final ascendió o disminuyó de categoría. PRINCIPALES MEDIDAS DE RESULTADO: Concordancia entre muestras obtenidas mediante biopsia y muestras completamente resecadas. RESULTADOS: La mediana de tamaño de lesiones fue de 3 cm (rango 1–11). En 189 casos (39%) las biopsias no proporcionaron un grado de displasia correcto en comparación con la patología final después de la resección completa. 143 casos (29%) y 46 casos (9%) ascendieron y descendieron de categoría, respectivamente. El porcentaje de casos con resultados de biopsia discordantes fue del 40% en los casos con una sola biopsia tomada y del 38% en los casos en los que se tomaron múltiples biopsias. El tiempo desde la biopsia hasta la resección completa no influyó en el resultado erróneo de las biopsias. Notablemente, el porcentaje de resultados de biopsia discordantes fue de 37% y 35% en lesiones que midieron 1–2 cm y 2–4 cm, respectivamente. Sin embargo, este porcentaje aumentó a 48% en lesiones colorrectales mayores de 4 cm. LIMITACIONES: Este estudio se diseñó para reflejar la rutina clínica, el número de biopsias obtenidas y la técnica de fórceps no fueron estandarizadas, lo que constituye una limitación. CONCLUSIONES: Este estudio demuestra que las biopsias con fórceps negativas a cáncer, de pólipos colorrectales grandes referidas para resección endoscópica, no son confiables. Teniendo en cuenta que la resección endoscópica de lesiones que contienen cáncer superficial es posible, el valor clínico de las biopsias con fórceps en lesiones aptas para la resección endoscópica es cuestionable. Vea el Resumen en video en http://links.lww.com/DCR/A984 .